(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2013)
تعد منطقة "الشرق الأوسط" من أكثر مناطق العالم توتراً ، و ترتبط هذه التوترات بشكل أساسي بوجود الكيان الصهيوني ككيان غاصب مزروع في قلب المنطقة، والذي يسعى إلى استغلال و سرقة أي أراضي وثروات تقع عليها يديه . ومع اكتشاف الاحتياطات الضخمة من الغاز و النفط في الحوض الشرقي للمتوسط تصاعدت حدّة التوترات في المنطقة بعد المساعي الإسرائيلية لاستغلال هذه الاحتياطات و سرقتها دون الأخذ بعين الاعتبار حقوق الأطراف الأخرى ، و هو ما أدّى إلى نشوب خلافات و صراعات ثنائية و متعددة الأطراف بين دول المنطقة ، تلعب "إسرائيل" فيها دوراً رئيسياً . وتشمل هذه الخلافات و الصراعات ، الصراع اللبناني – "الإسرائيلي" ، والخلاف التركي – القبرصي الذي تدخل فيه "إسرائيل" أيضاً كطرف ثالث . The "Middle East" is one of the most tense regions of the world, and these tensions linked mainly to the existence of the Zionist entity as an outside intity cruel implanted in the heart of the region, and which seeks to exploit and steal any land and wealth lies in his hands. And with the discoveries of reserves the vast gas and oil in the levant basin escalated tensions in the region after Israeli efforts to exploit these reserves and stealing these resourses without taking and this led to the outbreak of differences bilateral and multilateral conflicts of interests among the countries in the region which allows Israel to play a key role in these issues, especially the Lebanese – Israeli conflict ,the Turkish – Cyprios case which Israel is third party in such conflicts.